INVESTIGATING SITUATED LEARNING PRACTICE FOR ENGLISH LANGUAGE TEACHING IN HIGHER EDUCATION (ONLINE-BASED ENVIRONMENT) - Rizky Eka Prasetya (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2021)
In online-based contextual English language learning, learning must occur in its context, allowing English learners to seek and discover logical explanations for their knowledge via interaction with their non-physical and social distance environments. The purpose of the study is to explain and establish online-based situated learning in the English pedagogical context. The ethnography case study design employed the analysis with a collective case study type approach. The result exposed that situated learning affirmed to be implemented in online English learning contextual. Communities of practice implied a set of individuals with diverse interests and attitudes with similar purposes, and Skype, Zoom, Google Hangouts, Microsoft Teams were implied to be adaptable on this model. Authentic learning stresses actual activities that apply to real-world circumstances, and the model incorporated the Grammarly, Draftin, Scholastic Story Starters, Book Creator, and ReadWorks. The online language learning systematic model is designated to assess the quantity of material presented successfully in the course using online realistically, and it has Moodle, Google Classroom, Ispring Learn, and Microsoft Team. The last model finding is Task-Based Language Learning. Duolingo, Fabulingua, FluentU, and English Tools were the integrated online tools in the English pedagogical situated learning. Integrated and genuine situated learning of English language learning, online environments must allow English language learners to be competent performers with acquired information and collaborate on the essential communicative and technology literacy ability.